Screening of Punica granatum Seeds for Antibacterial and Antioxidant Activity with Various Extracts: A Brief Analytical Study - Khan, Naeem Hasan; Ying, Adriana Lee Tze; Tian, Candy Goo Zhi; Yi, Ooi Wei; Vijayabalan, Shantini (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
Punica granatum plant fruits best in areas with long, hot and dry summers (90°F) and cooler winters. Genus name comes from the Latin name contracted from Punicum malum. A 100-g serving of pomegranate seeds provides 12% of the Daily Value (DV) for vitamin C, 16% DV for vitamin K and 10% DV for folate. Pomegranate seeds are a rich source of dietary fiber (20% DV) which is entirely contained in the edible seeds. People who choose to discard the seeds forfeit nutritional benefits conveyed by the seed fiber and micronutrients [1]. The most abundant phytochemicals in pomegranate the hydrolyzable tannins called ellagitannins formed when ellagic acid and/or gallic acid binds with a carbohydrate to form pomegranate ellagitannins, also known as punicalagins [2,3]. The red color of juice can be attributed to anthocyanins. Generally, an increase in juice pigmentation occurs during fruit ripening [4]. The phenolic content of pomegranate juice is adversely affected by processing and pasteurization techniques [5]. The different extracts (maceration with ethanol and hexane separately and soxhlet with ethanol) were investigated for their antimicrobial activity (using agar well diffusion method). Penicillin and ampicillin were used as positive control. Ethanol soxhlet extracts showed good inhibitory effect over growth of all the seven strains of bacteria such that zone of inhibition was detected. Ethanol maceration extract only possessed antimicrobial activity against Neisseria gonorrhoeae, Pseudomonas aeruginosa and Staphylococcus aureus whereas hexane extract do not showed any antimicrobial activity. IC50, the half maximal (50%) inhibitory concentration for extracts of Punica granatum seed was calculated by using the equations obtained from the graphs. For the antioxidant activity, DPPH radical scavenging assay was performed. IC50, the half maximal (50%) inhibitory concentration was measured in this study. Ethanol soxhlet (ES) extract showed the lowest IC50 value (1350.27 \(μ\)g/mL); hexane extract (HM) showed IC50 value of 3005.66 \(μ\)g/mL and ethanol maceration extract (EM) showed highest IC50 value (4852.26 \(μ\)g/mL). To accomplish the aims, the following objectives were designed such as: Authentication of plant material. Evaluation of antimicrobial potential and antioxidant activity of various extracts of Punica granatum